Embracing exile: the case for Jewish Diaspora - Kraemer, David C. (Oxford University Press, 2025)
"Embracing Exile is a comprehensive history of Jewish responses to and conceptions of their exiles/diasporas. Jews have, since their beginnings, been a wandering people. According to their origin story, they wandered from Ur of Chaldees to Canaan to Egypt and then back to Canaan. From there, they were exiled to Babylon, where they built their longest-lived home, one that survived until the twentieth century. Over the span of centuries, they resettled in Persia, Egypt, Morocco, Spain, Italy, Turkey, Poland, Ukraine, and the United States, often flourishing. Thanks to these experiences, Diaspora became "natural" to Jews, and though they may have hoped for a return to their Promised Land at the End of Days, they made sense of their many homes, defending Diaspora as the realm where Jewish life could grow and Jews fulfill their covenantal obligations in the company of their God. The texts and expressions the volume documents in Defending Diaspora include biblical and rabbinic texts, philosophical treatises, Kabbalah, Hasidism, and a multiplicity of modern expressions. The book offers revised readings of the book of Esther and other biblical texts, a survey of Talmudic treatments of exile, an in-depth analysis of the thought of the Maharal of Prague, analyses of works by Philip Roth, and other modern authors, and much more. The book shows that lament has not been the most common Jewish response to diaspora and that Zionism is not the natural outcome of either Jewish ideology or history"-- Provided by publisher